2018
DOI: 10.1002/jcla.22656
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alpha thalassemia on clinical and laboratory parameters among nigerian children with sickle cell anemia

Abstract: This study confirms that coexistence of alpha thalassemia with SCA significantly influences both the clinical and laboratory manifestations of young Nigerian SCA patients. The coexistence of this genetic modifier is associated with increased bone pain crisis and protects against sickle leg ulcers among the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…The habitual Hb concentration in our patient was only moderately lowered (~9 g/dl), consistent with previous findings in patients with similar triplet mutations [9]. Reportedly, SCD patients who are heterozygote for HbS and alpha-thalassemia usually have mild hemolytic anemia [10,11]. In contrast, studies in SCD patients with concomitant G6PD have shown no clear effect regarding the degree of hemolytic anemia [12,13].…”
Section: Discussionsupporting
confidence: 90%
“…The habitual Hb concentration in our patient was only moderately lowered (~9 g/dl), consistent with previous findings in patients with similar triplet mutations [9]. Reportedly, SCD patients who are heterozygote for HbS and alpha-thalassemia usually have mild hemolytic anemia [10,11]. In contrast, studies in SCD patients with concomitant G6PD have shown no clear effect regarding the degree of hemolytic anemia [12,13].…”
Section: Discussionsupporting
confidence: 90%
“…Olatunya et al performed a cross-sectional retrospective study on 100 young Nigerian patients with SCA and 63 controls. Their study confirms that coexistence of alpha-thalassemia with SCA significantly influences both the clinical and laboratory manifestations with increased bone pain crisis and protection against leg ulcers [ 35 ].…”
Section: Discussionsupporting
confidence: 52%
“…α‐3.7 kb thalassemia deletion is the most common alpha‐thalassemia deletion in sub‐Sahara African populations and is a well‐known genetic modifier of SCA. Varied prevalence of α‐thalassemia deletion (‐α 3.7 ) has been reported from different populations among persons with SCA: 30% in Brazil, 37% in Cameroon, 41–43% in Nigeria, 48% in France, and 56% in Tanzania 10‐15 . Co‐inheritance of α 3.7 ‐thalassemia with SCA is associated with increased risk of avascular necrosis and vaso‐occlusive crises while it improves survival, reduces rate of leg ulcers, the need for blood transfusion, and stroke risk 11,16,17 .…”
Section: Introductionmentioning
confidence: 99%